Kajian Material Komposit Sandwich pada Floor Panel Pesawat Terbang - Muhammad Labib Adyavit; Larasati Irischa Ramadhani; Mardiyati Mardiyati; Steven Steven (Faculty of Mechanical and Aerospace Engineering, 2023)
Sandwich composites have been used as lightweight materials in aircraft manufacturing for a long time, from balsa wood sandwich in the 1930s to honeycomb and fiber-reinforced polymers sandwich. Its characteristics are considered as a 'perfect' material for aircraft, which has high strength with low density. Sandwich composites are the common materials for aircraft floor panels. The core is usually made of Nomex or aluminum honeycomb, while the skin is made of 1